School-based teacher training : a handbook for tutors and mentors - Jarvis, Joy; White, Elizabeth (Elizabeth J.) (SAGE, 2013)
Covering both primary and secondary teaching, this handbook offers support to those delivering school-based teacher training. By identifying best practice, the book shows you how to develop your professional knowledge and become an effective teacher educator and mentor.